2012
DOI: 10.1186/1471-2482-12-s1-s10
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and depression in a cohort of female patients with chronic disease

Abstract: BackgroundDifferences in health-related quality of life perception in patients with chronic disease may depend on pre-existing differences in personality profile. The purpose of the study was to investigate in a cohort of female patients with chronic diseases the relationship between the Quality of Life perception and the potential presence of depressive symptoms.Patients and methodsFemale patients with chronic diseases were enrolled in the study. Exclusion criteria were diagnosis of psychopathological conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
2
21
0
4
Order By: Relevance
“…Para esses autores, o agravamento de sintomas de dor que surgem em algumas doenças crônicas, em especial as relacionadas às condições osteomioarticulares, contribuem para a piora da qualidade de vida. Outro autor (4) avaliou a qualidade de vida de 57 mulheres que apresentavam sintomas de depressão, utilizando o questionário SF-36 e verificou que, destas, 43% apresentavam sintomas de doenças musculoesqueléticas, com baixos escores de qualidade de vida, principalmente ao analisar a dor. Pode-se inferir que a pior qualidade de vida observada no estudo, deve-se à presença de depressão entre as mulheres estudadas, pois os sintomas depressivos são, provavelmente, as respostas emocionais mais frequentes à dor e alteram a capacidade de se adaptar à vida social (21) .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Para esses autores, o agravamento de sintomas de dor que surgem em algumas doenças crônicas, em especial as relacionadas às condições osteomioarticulares, contribuem para a piora da qualidade de vida. Outro autor (4) avaliou a qualidade de vida de 57 mulheres que apresentavam sintomas de depressão, utilizando o questionário SF-36 e verificou que, destas, 43% apresentavam sintomas de doenças musculoesqueléticas, com baixos escores de qualidade de vida, principalmente ao analisar a dor. Pode-se inferir que a pior qualidade de vida observada no estudo, deve-se à presença de depressão entre as mulheres estudadas, pois os sintomas depressivos são, provavelmente, as respostas emocionais mais frequentes à dor e alteram a capacidade de se adaptar à vida social (21) .…”
Section: Discussionunclassified
“…O domínio saúde mental teve diferença significativa para doenças crônicas. Alguns estudos apontam que mulheres têm uma prevalência de ansiedade e de depressão, duas a três vezes maiores que os homens (4) . Observou-se também observaram redução significativa da qualidade de vida em indivíduos com doenças crônicas, corroborando com os resultados apresentados (15) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…1 One global mental health survey concluded that the highest incidence of depression among low and middle-income countries is found in Brazil. 2 Depression is the most frequent emotional response among people who suffer chronic illness 3,4 since this compromises an individual's functionality as well as his adaptation to social life.…”
Section: Introductionmentioning
confidence: 99%